A Course Applying Network Analysis to Organizational Risk in Information Security - Armstrong, Helen; Armstrong, Colin; McCulloh, I. (Centre for Security, Communications & Network Research, 2010)
Network science has been applied in the hard and soft sciences for several decades. Founded in graph theory, network science is now an expansive approach to the analyses of complex networks of many types of objects (events, people, locations, etc.). Researchers are finding that techniques and tools used in social network analysis have relevant application in projects that span more than just relationships between people. This paper discusses the application of network analysis in a postgraduate course on information security and risks in organisational settings as a special topic course.